The Impact of Waste Fluid Catalytic Cracking Catalyst Addition on the Selected Properties of Cement Pastes - Paweł Niewiadomski; Michał Cisiński (Materials Proceedings, 2023)
The significant reduction in CO2 emissions arising from the cementitious composites industry is one of the highest priorities for the construction sector’s movement towards climate neutrality and sustainable development. One of the approaches to cope with this issue is to partially substitute cement with supplementary cementitious materials. Recently, various oil refinery wastes (ORW) have attracted researchers’ attention in terms of being investigated for such an application. As such, the present paper shows the preliminary results of investigations conducted on cement pastes with the addition of a spent fluid catalytic cracking catalyst derived from a Polish oil refinery company. It is worth mentioning that the incorporation of ORW in cementitious composites might enable the production of more environmentally friendly construction materials without sacrificing quality, whilst, simultaneously providing an opportunity for recycling petrochemical wastes.